On the mechanism of the radiation effect at the cellular level - Lange, C (1967)
The effect of radiation on planarians, triclad platyhelminths known for their extensive powers of regeneration, has been studied with particular reference to the cellular basis of animal mortality probability. By reference to the literature we have shown that the planarian is an organism consisting of two cell populations: nonreplicating differentiated tissues interspersed with a population of morphologically identifiable stem cells. Postirradiation survival of the organism has been explained in terms of the rate of decay of function of the differentiated tissues and the reproductive integrity of the stem cell population. Factors known to influence planarian regenerative ability have been examined for their influence on mortality probability. Under standard conditions pre- and postirradiation, the change in per cent survivors as a function of radiation dose was taken as a measure of the reproductive integrity of the planarian stem cells. The survival of neoblast (stem cell) reproductive integrity for D. lugubris has been determined assuming a simple relationship between stem cell reproductive integrity and animal mortality probability (q.v. chapter VI), which necessitated the measurement of stem cell population size and repopulation probability (chapters VII and VIII respectively). This model represents the first successful quantitative description of animal mortality probability in terms of cellular reproductive integrity. [Please see pdf. for full abstract.]